Fructose-1, 6-bisphosphatase: From a glucose metabolism enzyme to multifaceted regulator of a cell fate. (May 2019) - Gizak, Agnieszka; Duda, Przemyslaw; Wisniewski, Janusz; Rakus, Dariusz
Abstract: Fructose-1, 6-bisphosphatase (FBPase) is one of the ancient, evolutionarily conserved enzymes of carbohydrate metabolism. It has been described for a first time in 1943, however, for the next half a century mostly kinetic and structural parameters of animal FBPases have been studied. Discovery of ubiquitous expression of the muscle isozyme of FBPase, thus far considered to merely regulate glycogen synthesis from carbohydrate precursors, and its nuclear localisation in several cell types has risen new interest in the protein, resulting in numerous publications revealing complex functions/properties of FBPase. This review summarises the current knowledge of FBPase in animal cells providing evidence that the enzyme merits the name of moonlighting protein.